Do flywheel exercises provide eccentric-overload training? - Spudic, D.; Nosaka, K. (Sports Medicine - Open, 2026)
Interests in eccentric resistance exercises have been increasing in both research and practice. However, implementing eccentric resistance exercise training is often challenging due to the mechanical limitations of traditional training equipment. To address this, flywheel (FW) devices emerged as a practical alternative. FW devices are commonly considered to provide eccentric-overload training, in which the load is greater in eccentric than concentric phase. However, this is not always the case. In this article, we summarize the mechanical and physiological factors influencing the effectiveness of FW devices in achieving eccentric overload. Then, we discuss a significant limitation of FW resistance exercise in accurately quantifying the load, since eccentric mechanical load is constrained by preceding concentric phase. Lastly, we explore potential practical solutions and improvements in research methods for FW resistance exercises. FW resistance exercises become eccentric-overload exercises only when higher mechanical quantities are achieved and confirmed during the eccentric than in the concentric phase of repetitions. It is important to examine if eccentric overload is actually achieved during training and testing, which can clarify if the eccentric overload is a key factor for the neuromuscular adaptations observed following a FW resistance training.